Epidemiology of accident and safety concern during arba’een Karbala pilgrimage of 2024: An observational analysis - Bonyan, Fadil Agla; Al-Ghuzi, Ali Abid Saadoon; Naqvi, Syed Yaseen; Al-Hayawi, Ibrahim Saeed Katih Mahdi (Journal of the Pakistan Medical Association, 2025)
Objective: To analyse the distribution and characteristics of accidents during the Arba’een pilgramage. Method: The retrospective, descriptive study was conducted at the Ministry of Health, Baghdad and Karbala and comprised data from July 26 to August 26, 2024 related to accidents during the Arba’een pilgrimage in Karbala, Iraq. The data was obtained from health directorates across Iraq. The incidents were categorised by type, health department, and pilgrim nationality (Iraqi or foreign). The distribution of injuries and fatalities was assessed. Data was analysed using SPSS version 26. Results: Of the 728 injuries recorded, 681(93.54%) involved Iraqi nationals and 47(6.46%) involved foreign pilgrims (p=0.0051). Of the 19 fatalities reported, Iraqi pilgrims accounted for 12(63.2%) and foreign pilgrims 7(36.8%) (p=0.00018). Falls, fractures, and road traffic accidents were the most common injury types. High-risk regions, such as Karbala and Najaf, received significant resource allocation, including medical personnel and emergency response services. Conclusions: Different types of injuries and fatalities during the Arba’een pilgrim mostly affected Iraqis, and the most common type of incidents was road traffic accidents. Key Word: Accidents, Safety, Arba’een pilgrimage.